Artificial Intelligence in Healthcare: Opportunities and Difficulties - Ritu Arora; Anjali Banga (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The usage of Artificial Intelligence (AI) into the healthcare system gains the potential to increase efficiency, speed up the diagnostic processes & improve result quality. Having said that, using the instruments in the healthcare environment in conjunction with growth of its uses, the issue of adherence to laws, morals, and regulations comes up. Therefore, the ethical, legal, and responsibility issues that come up when AI is used in healthcare have been reviewed in this review article. These issues include privacy, algorithm bias, transparency, accountability, and weakened doctor-patient relationships. Liability, the numerous legal gaps that exist, and intellectual property rights are the key legal areas of concern. To address these expanding legal difficulties, legal frameworks must be created. The author of the article emphasizes the idea on AI’innovations and responsibility; as a result, he urges regulatory bodies to develop a methodical and strategic approach to AI, encourage AI to express their opinions, and create strategies to combat bias through diversity of data. Additionally covered are patient-centered AI use, roles and duties in the event of injury, and continuous monitoring of AI systems. These steps are intended to guarantee that the usage of AI in healthcare remains appropriate, effective and harmless to lessen adverse effects and enhance patient outcomes. To accomplish this, it emphasizes the importance of patient security as a vital basis for the successful use of the researched artificial intelligence usages in the healthcare sector, as well as the necessity of proactive government regulation, the engagement of all interested stakeholders and the necessity of proactive government regulation. The conclusion reiterates the notion that AI must be positioned as a device for positive deviations in the current healthcare delivery organization that must be cast-off in compliance with the primary ethical and legal guidelines.